Domestic tourist satisfaction and perceived quality of Kelantan food - Muhammad Iznul Fahmi Husaidi; Muhammad Anas Rosli; Lim Jing Xuan; Tey Jin Wen (2021)
Food tourism an important segment in the Malaysian Tourism industry, however, relate to tourist satisfaction towards the quality of food is limited. This research examines tourists’ satisfaction towards the quality of Kelantanese food. The study employs the quantitative research design using a survey questionnaire. Probability sampling was employed as simple random sampling from the population size of 3.1 million peoples. From this, a total 392 domestic tourists who had previously visited Kelantan were invited and participate in this study. The results of this study indicate that food image, food tourism and food quality have a significant relationship to tourist satisfaction. The study also reveals that food quality is a major indicator which satisfies the domestic tourists who visit Kelantan. The study provides some insights for policy implication with regards to food tourism development in Malaysia.